2012
DOI: 10.1038/emboj.2012.155
|View full text |Cite
|
Sign up to set email alerts
|

The B-cell identity factor Pax5 regulates distinct transcriptional programmes in early and late B lymphopoiesis

Abstract: Pax5 controls the identity and development of B cells by repressing lineage-inappropriate genes and activating B-cell-specific genes. Here, we used genome-wide approaches to identify Pax5 target genes in pro-B and mature B cells. In these cell types, Pax5 bound to 40% of the cisregulatory elements defined by mapping DNase I hypersensitive (DHS) sites, transcription start sites and histone modifications. Although Pax5 bound to 8000 target genes, it regulated only 4% of them in pro-B and mature B cells by induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
211
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(226 citation statements)
references
References 60 publications
13
211
0
2
Order By: Relevance
“…PAX5 binds directly to thousands of DNA sites in B cells and functions by both activating and repressing gene expression [40]. During early B cell development PAX5 is absolutely required for the initial commitment of lymphoid progenitors to the B cell fate [43] and V-DJ recombination of the Ig locus [44,45].…”
Section: Pax5mentioning
confidence: 99%
See 2 more Smart Citations
“…PAX5 binds directly to thousands of DNA sites in B cells and functions by both activating and repressing gene expression [40]. During early B cell development PAX5 is absolutely required for the initial commitment of lymphoid progenitors to the B cell fate [43] and V-DJ recombination of the Ig locus [44,45].…”
Section: Pax5mentioning
confidence: 99%
“…During early B cell development PAX5 is absolutely required for the initial commitment of lymphoid progenitors to the B cell fate [43] and V-DJ recombination of the Ig locus [44,45]. In mature B cells it regulates the expression of genes critical to B cell identity, including components of the B cell receptor (Ig heavy chain and CD79A), CD19, CD21, B lymphocyte kinase (BLK), interferon regulatory factor (IRF)4 and IRF8 [40]. In addition, PAX5 further reinforces B cell identity by repressing the expression of lineage inappropriate genes, including Fmslike tyrosine kinase 3 (FLT3), CCR2 and CD28, which are expressed in PCs following PAX5 down-regulation, and macrophage colony-stimulating factor (M-CSF) receptor, NOTCH1, RAMP1, LMO2 and CCL3, which are expressed in common lymphoid progenitors and myeloid cells [46].…”
Section: Pax5mentioning
confidence: 99%
See 1 more Smart Citation
“…The principal defects were observed in the B cell lineage; among them, alteration of peritoneal B-1 cell development, and decreased serum and mucosal antibody production (62). Further data pointing to an important role for Bst1 in B lymphocyte development and migration is that the Bst1 gene has been identified as a target of the transcription factor Pax5, the B-cell identity factor, in murine pro-B cells (63).…”
Section: The Vertebrate Adp-ribosyl Cyclasesmentioning
confidence: 99%
“…Analysis of gene expression of wild-type and PAX5 knock-out pro-B cells revealed that 110 and 170 genes are repressed and activated, respectively, by PAX5 and that these genes encode essential proteins that participate in several important cell process. PAX5 regulates expression of these genes through induction or elimination of active chromatins (Revilla-i-Domingo et al, 2012). Importantly, PAX5 has also been associated with human B-cell tumors.…”
Section: Introductionmentioning
confidence: 99%